2022
DOI: 10.3390/agronomy12081834
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Treatment Influence on Selected Nutritional Values of Common Sea Buckthorn (Hyppophae rhamnoides) Juice

Abstract: Since ancient times, sea buckthorn (Hyppophae rhamnoides) (SBT) has been utilized as a medical plant for its ability to extract health-promoting compounds from its fruits, seeds, pulp, skin, bark, roots, and leaves. L-ascorbic acid is primarily found in fruits, and because of this, it can be utilized as a fortification agent to enhance other juices. The study’s goal was to look into how the L-ascorbic acid and selected nutritional parameters in common sea buckthorn juice changed over the period of storage and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
3
1
0
Order By: Relevance
“…They found out that the content of vitamin C did not change depending on the temperature and duration of pasteurization. The same observation was found also by Mezey et al ( 76 ) who have studied the impact of (i) the modified VAT pasteurization process, presenting a single pasteurization (treatment at 85°C for 5 min) and the double pasteurization approach (treatment at 85°C for 5 min, then cooling down to 5°C and immediate treatment for 5 min at 85°C), and (ii) sterilization at 120°C for 3 min. However, worth to notice that some studies have also reported a significant loss of vitamin C. Manea and Buruleanu ( 78 ) observed an almost 86% decrease in vitamin C content during a 3-month storage period at refrigeration conditions in thermal pasteurized sea buckthorn juices.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…They found out that the content of vitamin C did not change depending on the temperature and duration of pasteurization. The same observation was found also by Mezey et al ( 76 ) who have studied the impact of (i) the modified VAT pasteurization process, presenting a single pasteurization (treatment at 85°C for 5 min) and the double pasteurization approach (treatment at 85°C for 5 min, then cooling down to 5°C and immediate treatment for 5 min at 85°C), and (ii) sterilization at 120°C for 3 min. However, worth to notice that some studies have also reported a significant loss of vitamin C. Manea and Buruleanu ( 78 ) observed an almost 86% decrease in vitamin C content during a 3-month storage period at refrigeration conditions in thermal pasteurized sea buckthorn juices.…”
Section: Resultssupporting
confidence: 81%
“…The mean content of ascorbic acid in Leikora variety treated syrups (Figure 1) was 134 ± 3 mg/100 g of syrup (untreated syrup 133 ± 6 mg/100 g) and Botanica variety treated syrups was 70 ± 3 mg/100 g of syrup (untreated syrup 69 ± 5 mg/100 g). The values were comparable with those presented in literature (13,76). Our results confirmed also other studies, where different pasteurization conditions were applied to sea buckthorn juices.…”
Section: Impact Of Treatments On Bioactive Compoundssupporting
confidence: 92%
See 1 more Smart Citation
“…This situation in HTHP can also be found in sea buckthorn juice (Jasniewska et al., 2021). The reason may be that the water vapor contained in the SCJ evaporates during the heating process, which objectively increases the concentration of sugar in it (Mezey et al., 2022). The presence of sucrose is mostly responsible for the lower sugar content.…”
Section: Resultsmentioning
confidence: 99%